Feasibility of banana (Musa paradisiaca L.) cultivation under Banswara district conditions of Rajasthan (IASH Indian Journal of Arid Horticulture, 2024)
An experiment was conducted at seven locations denoted as AF1 , AnF1 , AnF2 , LF1 , MF1 , SF1 and IF1 respectively to study the feasibility of banana cultivation under Banswara district conditions of Rajasthan which are very much milder than that in the desert regions in further north and north-west Rajasthan and also commensurate with the required environmental conditions for banana. For this, phenology of banana cv. Grand Naine was studied by observing the growth pattern. At harvest the vegetative parameters such as range of leaf area varied from 1.21 m2 (IF1 ) to 5.52 m2 (AnF1 ) per plant, number of functional leaves varied from 5.03 (IF1 ) to 10.03 (AnF1 ), pseudostem height from 131.18 cm (IF1 ) to 203.37 cm (AnF1 ), pseudostem girth from 39.65 cm (IF1 ) to 59.38 cm (AnF1 ). Likewise, yield and yield attributing characters were also observed such as peduncle length from 33.96 cm (IF1 ) to 45.01 cm (AnF1 ), bunch weight from 8.42 kg (IF1 ) to 17.06 kg (AnF1 ), number of hands per bunch from 6.56 (IF1 ) to 8.76 (AnF1 ), number of fruits per hand from 10.63 (IF1 ) to 14.04 (AF1 ), fruit length from 12.68 cm (IF1 ) to 16.11 cm (AF1 ), fruit diameter from 2.37 cm (IF1 ) to 3.35 cm (AnF1 ), fruit weight from 90.75 g (IF1 ) to 118.30 g (AF1 ) and estimated yield per hectare from 25.98 t (IF1 ) to 52.65 t (AnF1 ). The study of crop duration had shown values which varied from 292.74 (AnF1 ) to 307.03 days (IF1 ) for shooting, fruits attained the physiological maturity after flower emergence from 105.84 days (AnF2 ) to 114.34 days (IF1 ) and plants completed their life cycle in 398.63 days (AnF2 ) to 421.37 days (IF1 ). The parameters pertaining to quality of fruits were also studied such as TSS (ºBrix), titrable acidity (%) and organoleptic rating which ranged from 11.57 (IF1 ) to 14.48 (AnF2 ), 0.126 (AnF1 ) to 0.196 (SF1 ) and 6.95 (IF1 ) to 7.64 (AnF2 ), respectively. The results of the experiment proved that Banswara conditions are ideally suited for banana cultivation and the yield and quality of the fruits was at par with those of other locations in the country where banana cultivation is commercially practiced.